Peran Teologi Islam dalam Resiliensi Kesehatan Mental Remaja Generasi Z - Tika Putri Yasmin; Joni Harnedi; Irhas (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
The mental health of Generation Z adolescents is under serious pressure due to technological developments, value disruption from globalization, and the impact of the COVID-19 pandemic. This phenomenon is marked by increasing symptoms of anxiety, stress, and depression, which are often not addressed holistically. This article explores the potential of Islamic theology as an integrative approach to healing the mental health of Gen Z adolescents. Using a literature review method covering sources from 2020–2025, the study finds that Ilmu Kalam principles such as tawhid (divine oneness), qadar (destiny), and the wisdom behind trials provide a profound rational-spiritual framework for understanding suffering and fostering psychological resilience. Practices such as dhikr (remembrance of God), tawakkul (trust in God), patience, and Islamic counseling-based therapy show significant effectiveness in improving adolescents' mental well-being. However, the implementation of Ilmu Kalam faces challenges, including social stigma, the complexity of theological language, and a lack of youth-friendly digital platforms. Therefore, adaptive strategies such as the digitalization of Islamic theology content, multidisciplinary collaboration, and strengthened intervention research become crucial.